2012
DOI: 10.1177/193229681200600402
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast-Acting Insulins: State of the Art

Abstract: Abbreviations: (AP) artificial pancreas, (ARIA) alternative routes of insulin administration, (CGM) continuous glucose monitoring, (CSII) continuous subcutaneous insulin infusion, (FDA) Food and Drug Administration, (GIR) glucose infusion rate, (GV) glycemic variability, (HbA1c) hemoglobin A1c, (HGP) hepatic glucose production, (ID) intradermal, (IMI) injection-meal interval, (NDA) new drug application, (PD) pharmacodynamic, (PK) pharmacokinetic, (PPG) postprandial glycemic excursion, (RAIA) rapid-acting insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 78 publications
2
89
0
12
Order By: Relevance
“…These include micro-needle, intradermal infusion sets for pump therapy, [12][13][14][15] changes in excipients in RAIA formulations to accelerate insulin molecule monomerization 16 and treating the insulin infusion site with hyaluronidase to breakdown interstitial barriers to dispersion of injected liquids. 17 In comparison to these approaches, local warming relies on a relatively simple physiological approach which, in this study, we have demonstrated is suited for injection as well as pump therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These include micro-needle, intradermal infusion sets for pump therapy, [12][13][14][15] changes in excipients in RAIA formulations to accelerate insulin molecule monomerization 16 and treating the insulin infusion site with hyaluronidase to breakdown interstitial barriers to dispersion of injected liquids. 17 In comparison to these approaches, local warming relies on a relatively simple physiological approach which, in this study, we have demonstrated is suited for injection as well as pump therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Linjeta jest preparatem złożonym z ludzkiej insuliny krótkodziałającej, kwasu etylenodiaminooctowego i cytrynowego. Taki skład, powoduje odłączenie jonów cynkowych od cząsteczek insuliny i zapobiega ich agregacji w heksamery, dzięki czemu insulina pozostaje w postaci monomerów i znacznie szybciej się wchłania [4,5]. Porównując wpływ insuliny Linjeta, Lispro oraz insulin ludzkiej szybkodziałającej na glikemię poposiłkową u pacjentów z cukrzycą typu 1 uzyskano istotnie niższe wartości w grupie Linjeta (0-180 min; 157 ± 30 mg/dl; p = 0.002 vs. insulina ludzka szybkodziałająca) i w grupie Lispro (170 ± 42 mg/dl; p = 0.668 vs. insulina ludzka szybkodziałająca).…”
Section: Ultraszybkodziałające Analogi Insulinunclassified
“…Linjeta is a formulation containing short-acting human insulin, EDTA, and citric acid. These components result in hexameric insulin dissociation into insulin monomers and a more rapid insulin absorption [4,5].…”
Section: Rapid-acting Insulinmentioning
confidence: 99%
“…A 52-week study of glargine insulin and Technosphere inhaled insulin used together lowered A1C from 8.7% to 8.0% (21). In contrast, A1C values in a study of injected basal-bolus insulin fell from 8.1-8.3% to 6.5-6.7%, but with substantial weight gain and hypoglycemia (22).…”
mentioning
confidence: 91%
“…As such, inhaled insulin is still a convenience product rather than a proven advance in insulin therapy. However, it is at the forefront of several faster insulins that are in development (22,23). And the question remainsdis faster better?…”
mentioning
confidence: 99%